Software certification implementation: Case studies analysis and findings - Yahaya, Jamaiah; Deraman, Aziz; Hamdan, Abdul Razak (2008)
Continuous improvement in software quality is an essential concern in software industry. One way to guarantee this continuous improvement is through imposing certification environment. Current studies show that certification of software products are feasible and demonstrate the practicality of the implementation in real situation. Two main models were developed based on end product and process development approach of certification. These models have been tested in three real case studies involving three large organizations in Malaysia. The result of the studies shows that the proposed models and underlying attributes and metrics are appropriate to be gathered and collected during assessment and certification exercises. By having a successful applicable of the case studies show that the models are feasible and practical in the real world environment. Favourable evaluations from the organisations via the software owners enrich the validity and integrity of the model. This paper focuses on implementation of certification model by end product quality approach.